Study of geostatistical functions applied to automatic eye detection. (1st January 2012) - Almeida, J.D.S.; Silva, A.C.; Paiva, A.C.
Several computational systems that depend on the precise location of the eyes were developed in the last decades. Aware of this need, we propose a method for automatic eye detection in images of human faces using geostatistical functions (semivariogram, Getis index, Moran's index and Geary's coefficient) and support vector machines. The geostatistical measures are used as input features for a support vector machine classifier with the purpose of distinguishing patterns of eyes region and other areas of the face. The method was tested with ORL human face database, which contains 400 images of 40 persons, having ten different expressions for each person. The use of the proposed techniques showed to be very promising, since we obtained results of sensitivity of 92.2% for Moran's index, specificity of 93.4% and accuracy of 88.45% for semivariogram function.